Satisfaction and Determinants of the Decision to Switch from Private Vehicles to Commuter Trains in Merak–Rangkasbitung - Mahendra, Muhammad Oka; Djuneydi, Muhammad (Kadiri University, 2025)
Urban population growth has had an impact on traffic congestion. Although public infrastructure is available, public preference for private vehicles remains high. This occurs on the Merak-Rangkasbitung route which is served by the train. The gap between service availability and user preferences indicates the need to study mode selection behavior and the factors that influence it. This study aims to analyze motorcycle and car users' tendency to shift their transportation modes from private vehicles to the train service on the Merak- rangkasbitung route. A quantitative approach was carried out using a questionnaire survey method on 300 respondents using a dual-stratum sampling technique. The analysis used the Importance Performance Analysis (IPA), Customer Satisfaction Index (CSI), and Chi-Square test. The IPA results showed a service suitability value of 86.57%, while CSI showed a satisfaction level of 72.86% (satisfied category). The Chi-Square test results identified that the factors influencing the transportation mode choice differed between segments. For motorcycle users, it was influenced by age, car ownership, and reason for travel, while car users were influenced by occupation, travel costs, reasons and purposes of travel. These findings emphasize the importance of a policy approach based on user segmentation and strengthening integration between modes to improve the effectiveness of train services. With an adaptive service strategy and targeted incentive policies, the transformation towards sustainable urban mobility can be realized.